PENGARUH PROFITABILITAS PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN MANUFAKTUR DARI TAHUN 2014-2018 - Yoas Yoas; Emilia Dewiwati Pelipa; Yunita Astikawati (STIE 'INDONESIA' Pontianak, 2020)
The study was conducted to determine the effect of company profitability on firm value. Company profitability is measured using the Return on Assets (ROA) approach. Company value is measured using Tobins Q. The research method used is quantitative methods. The population in this study is a manufacturing company listed on the IDX in the basic industry and chemical sector in 2014-2018 consisting of 72 companies with a sample of 42 companies consisting of 240 financial statements. The data collection technique is the study of documentation. The data collection tool in this study is in the form of company financial statement documentation, data processing techniques using a simple regression test obtained regression coefficient value of 0.040, t test based on the calculation results is known t hitung> t tabel or 2.676> 1.969. means Ha is accepted H0 is rejected. So it can be concluded that there is a significant effect between the company's profitability on the value of the company.